Odpowiedzi

Najlepsza Odpowiedź!
2009-12-11T19:24:21+01:00
{xy+5y-2x-10=xy+2y-x-2 /-xy+x-2y+10
{xy-4y+7x-28=xy-3y+4x-12 /-xy+3y-4x+28

{3y-x=8
{-y+3x=16 /*3

{3y-x=8
+{-3y+9x=48

{8x=56 /:8
{3y-x=8

{x=7
{3y-7=8 /+7

{x=7
{3y=15 /:3

{x=7
{y=5
2009-12-11T19:32:07+01:00
(x+5)(y-2)=(x+2)(y-1)
(x-4)(y+7)=(x-3)(y+4)

1.
xy-2x+5y-10=xy-x+2y-2
xy-xy-2x-2y+5y+x=-2+10
-x+3y=8

2.
xy+7x-4y-28=xy+4x-3y-12
xy-xy+7x-4y-4x+3y=-12+28
-y+3x=16


-x+3y=8
-y+3x=16

-x=8-3y I*-1
-y+3x=16

x=-8+3y
-y+3x=16

x=-8+3y
-y+3(-8+3y)=16

x=-8+3y
-y-24+9y=16

x=-8+3y
8y=16+24

x=-8+3y
8y=40 ÷8

x=-8+3y
y=5

x=-8+3*5
y=5

x=-8+15
y=5

x=7
y=5



* znak mnożenia